Pendidikan Bagi Generasi Milenial di SMA Almanar Azhari Islamic Boarding School Depok, Jawa Barat - Diana Riyana Harjayanti; Endang Susilo Wardani; Oki Ikbal Khair; Nelwati Tanius; Reza Octovian (Indonesian Journal of Society Engagement, 2020)
Islamic education is sourced from the Qur'an and the Hadith of the Prophet SAW aims to form a complete human being, namely people of faith and pious to Allah SWT and to maintain the values ??of the lives of fellow human beings so that they can carry out their entire lives as determined by Allah SWT and the Apostles- Him, for the happiness of living in this world and the hereafter. To understand the nature of Islamic education, one must understand the historical elements of Islamic education itself. Studying the history of Islamic education is very important especially for Islamic religious students and Islamic leaders in this era of globalization and in this millennial era. Where technology is increasingly advanced, communication in cyberspace (the internet) is increasingly being accepted and spread in various regions and at all age levels. So by studying the history of Islamic education (the time of the Prophet Muhammad and the Khulafaurrasyidin) will be able to find out the cause of the progress and decline of Islam both from the way of education and the way of teaching. Abstrak Pendidikan Islam bersumber dari Al-Qur’an dan Hadits Nabi SAW bertujuan untuk membentuk manusia seutuhnya, yakni manusia beriman dan bertakwa kepada Allah SWT serta untuk memelihara nilai-nilai kehidupan sesama manusia agar dapat menjalankan seluruh kehidupannya sebagimana yang telah ditentukan Allah SWT dan Rasul-Nya, demi kebahagiaan hidup di dunia dan di akhirat. Untuk memahami hakikat pendidikan Islam, maka harus memahami unsur historis pendidikan Islam itu sendiri. Mempelajari sejarah pendidikan Islam sangatlah penting terutama bagi pelajar-pelajar agama Islam dan pemimpin-pemimpin Islam pada era globalisasi dan di zaman milenial ini. Dimana teknologi semakin maju, komunikasi di dunia maya (internet) semakin cepat diterima dan tersebar di berbagai daerah dan ditingkat semua umur. Sehingga dengan mempelajari sejarah pendidikan Islam (masa zaman Nabi Muhammad SAW dan masa Khulafaurrasyidin) akan dapat mengetahui sebab kemajuan maupun kemunduran Islam baik dari cara pendidikannya maupun cara ajarannya. Kata Kunci: pendidikan; islam; generasi milenial